A blade-like CoZn metal organic framework-based flexible quasi-solid Zn-ion battery. Issue 18 (13th February 2023) - Zhu, Yajun; Han, Tianli; Lin, Xirong; Zhang, Huigang; Hu, Chaoquan; Liu, Jinyun
Abstract : We develop a blade-like CoZn metal organic framework-based flexible quasi-solid secondary battery, which is applicable for wearable devices such as foldable cellphones and pads. Abstract : Wearable flexible electronics has become more and more significant and popular in daily life. Here, a flexible quasi-solid Zn-ion battery consisting of CoZn-metal organic frameworks (MOFs) grown on carbon cloth as an all-in-one cathode working with a hydrogel electrolyte is developed. CoZn MOFs display a blade-like morphology, which is significant for rapid transfer of ions and electrons. The battery bending at angles from 0° to 180° displays high capacities and good capacity retention, and the capacity remains stable as the flexible battery twists to 90°. In addition, the capacity exceeds 101.4 mA h g −1 as the battery is folded to 180° for 30 times, which indicates that the developed Zn-ion batteries would be applicable for a large variety of wearable devices such as foldable cellphones and pads.